Recovery of motor coordination after exercise is correlated to enhancement of brain-derived neurotrophic factor in lactational vanadium-exposed rats. (23rd July 2015) - Wang, Dean-Chuan; Lin, Yu-Yi; Lin, Hwai-Ting
Highlights: Lactational vanadium exposure impairs motor coordination in the late adolescent male rats. Exercise during childhood-adolescence prevents the impairment of motor coordination. We find a strong correlation between enhanced BDNF level and improvement of motor coordination. Abstract: Lactational exposure to vanadium can reduce the locomotor activity in adult animals. In this study, we investigated whether lactational vanadium exposure impairs the motor coordination and whether exercise ameliorates this dysfunction. Sprague–Dawley dams were treated with or without vanadium during lactation. The weaned male offspring were trained to treadmill running for 5 weeks and then examined their motor coordination on a rotarod. The neuroprotective effect of exercise was evaluated by the brain-derived neurotrophic factor (BDNF) in plasma and cerebellum. The results demonstrated that vanadium-exposed rats exhibited impaired motor coordination and reduced plasma and cerebellar BDNF levels. Treadmill running during childhood-adolescence prevented the impaired motor coordination in the lactational vanadium-exposed rats. The beneficial effect of treadmill running on motor coordination in the vanadium-exposed rats was correlated to the normalization of plasma and cerebellar BDNF levels, as well as the increased TrkB phosphorylation in the cerebellum. The result suggests that exercise may prevent the impairment of motor coordination in the lactational vanadium-exposed rats.